1994
DOI: 10.1080/09553009414550451
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Human Melanoma Xenograftsin Vivo: Proton Spin—lattice and Spin—spin Relaxation Times Versus Fractional Tumour Water Content and Fraction of Necrotic Tumour Tissue

Abstract: Proton nuclear magnetic resonance (1H-nmr) imaging is used routinely in clinical oncology to provide macroscopic anatomical information, whereas its potential to provide physiological information about tumours is not well explored. To evaluate the potential usefulness of 1H-nmr imaging in the prediction of tumour treatment resistance caused by unfavourable microenvironmental conditions, possible correlations between proton spin-lattice and spin-spin relaxation times (T1 and T2) and physiological parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
45
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 99 publications
3
45
0
Order By: Relevance
“…Consequently, addition of soluble proteins dose-dependently decreased T 1 (15). Studies of untreated human melanoma xenografts showed that tumor T 1 was correlated positively with extracellular tumor water content (16,(18)(19)(20) and proliferation (21), but negatively with necrosis (18,19). Theoretically, cell destruction would lead to the release of macromolecules and denatured proteins, as well as paramagnetic ions from damaged erythrocytes and thus reduce T 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, addition of soluble proteins dose-dependently decreased T 1 (15). Studies of untreated human melanoma xenografts showed that tumor T 1 was correlated positively with extracellular tumor water content (16,(18)(19)(20) and proliferation (21), but negatively with necrosis (18,19). Theoretically, cell destruction would lead to the release of macromolecules and denatured proteins, as well as paramagnetic ions from damaged erythrocytes and thus reduce T 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies using a different method showed that the T 1 of experimental tumors was greater than in normal tissue and was considered to reflect predominantly the extracellular space (14)(15)(16)(17), with a larger interstitial compartment giving a longer (higher) T 1 . In untreated tumors, a low tumor T 1 has been correlated to increased necrosis (16,18), low water content (14)(15)(16)(17)(18)(19)(20), high levels of soluble protein (15), and low proliferation (21). Animals treated with chemotherapy or radiotherapy showed increases (22)(23)(24) and decreases (15,25) in tumor T 1 .…”
mentioning
confidence: 99%
“…The proton spin-lattice and spin-spin relaxation times (T1 and T2, respectively) in tumours are influenced significantly by the fraction of free to bound water and the presence of paramagnetic ions (Braunschweiger et al, 1986;Negendank et al, 1991). The possibility has therefore been suggested that viable and necrotic regions in tumours might differ in T, and T2 (Banard et al, 1986;Belfi et al, 1991) and hence that MRI might be developed to be an efficient method for detection of necrotic regions in tumours (Dodd et al, 1989;DeJordy et al, 1992;Rofstad et al, 1994). Several in vitro studies of tumour cells and tissues have given results supporting this suggestion (Bakker and Vriend, 1983;Englund et al, 1986;Sillked et al, 1990).…”
mentioning
confidence: 99%
“…
(Hawkins and Phelps, 1988;Steen, 1992).Proton nuclear magnetic resonance imang (MRI) is well established as a diagnostic method in clnical oncology, but has been devoted less attention as a potential method for providing information on metabolic and physiological conditions in tumours (Steen, 1992;Rofstad et al, 1994). The proton spin-lattice and spin-spin relaxation times (T1 and T2, respectively) in tumours are influenced significantly by the fraction of free to bound water and the presence of paramagnetic ions (Braunschweiger et al, 1986;Negendank et al, 1991).
…”
mentioning
confidence: 99%
See 1 more Smart Citation